Research on resource service matching in cloud manufacturing. (January 2018) - Zhang, Ming; Li, Chunquan; Shang, Yuling; Li, Cailin
Abstract: Resource Service Matching is one of the key issues in Cloud Manufacturing, which is the latest mode of network manufacturing. In this paper, Resource Service Matching for aggregated resources with capacity restraint is discussed. Genetic Algorithms is proposed to search the best matching result for the request of customers, which assure the total cost and time of all the tasks is the lowest. In order to avoid premature evolution of populations, a novel approach of Genetic Algorithm is proposed in this paper. It is indicated by the results of simulation that the improved algorithm worked efficiently in Resource Service Matching.